Implementation Of Public Service Digitization Policy In Gubeng Urban Village, Gubeng Sub-District Surabaya City (Study Of Surabaya Single Window (Ssw) Alfa Imlementation In Providing Public Services) - Jefri Arditya Pamungkas (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2024)
Surabaya Single Windows (SSW) Alfa is an innovation program for licensing and non-licensing services from the Surabaya City Government. Surabaya Single Windows Alfa is a development application from a previous application called Surabaya Single Windows which was launched in 2013. With the SSW Alfa application, residents of the city of Surabaya can process service requests online. Gubeng Village consistently serves residents by using the digitalization system provided by the Surabaya City Government. The aim of this research is to describe the implementation of the Surabaya Single Windows Alfa digitalization service program in Gubeng Village, Gubeng District, Surabaya City based on the theory of Successful Program Implementation according to George Edward III which consists of Communication, Disposition, Resources and Bureaucratic Structure. The method used in this research is descriptive qualitative by collecting observation and interview data. The research results show that the Surabaya Single Windows Alfa program has been running well. However, in its implementation there are still several obstacles that hinder the implementation of the program. The inhibiting factors found in this research are the need for equal understanding of the application of Surabaya Single Windows Alfa for human resources in Gubeng Village and the lack of socialization to the community regarding the Surabaya Single Windows Alfa program. This results in many people still not understanding the terms or documents required for the application.